CONTEXT : the effects of environment on product design and evaluation. (WOODHEAD, 2019)
Context: The Effects of Environment on Product Design and Evaluation addresses the environment, or context, in which we consume products and the impact of context on choice and acceptability. The book explores what context is, how it influences design by specialists, and acceptance by consumers. Chapters discuss the basics of context, food and drink in context, testing a range of other products, and other contextual variables. Historically, research on context has been done in the laboratory and various natural locations, but rapid growth in other methods to study context, including evoked contexts, immersive contexts, virtual reality contexts, and more have widened research possibilities. Appealing to the professional, academic and commercial markets, this book will be of interest to those who conduct research in product development and product testing, to those who study what controls product usage, including eating from the health perspective, and to those who make decisions about product and space development.